The COVID-19 and integration in the face of the challenges of a new world order (2021)
When the pandemic passes, a fundamental post-pandemic stage comes in which we must face the profound changes in the International System that will lead to a new world order. These changes cover various fronts such as economics and geopolitics, social or environmental, and an instrument such as integration must be prepared to address these challenges in a cooperative, supportive, and consensual manner. In the economicsphere, there is a revaluation of the actions of the States through public policies, initially oriented primarily towards health, but which will lead to other issues of social policy in the field of employment, economic reactivation through new forms of productive chains and of establishing public policies aimed at prioritizing measures corresponding to a Welfare State, where the objectives of sustainable development acquire priority, as well as all the policies related to environmental problems. These measures will be accompanied by a revaluation of multilateral management through institutional reforms and global agreements, influenced at the same time by a great dispute of world leadership between the United States and China, but in a context of regionalization with different areas of the planet playing a leading role, such as East Asia and the Middle East. The countries of Latin America will achieve little individually and in a disorganized manner, which is why a challenge in the post-pandemic is to reactivate their integration processes to meet the enormous needs and requirements that must be addressed as well as possible. Academic researchers who are members of the Reflection Group on Integration and Development in Latin America and Europe - GRIDALE participate with their analysis of these challenges of a new world order as a consequence of COVID-19.